Clinical analysis of 30 cases of cardiac cephalalgia. (August 2022) - Xu, Jia; Mao, Ningning; Wang, Chengze; Feng, Jilun; Lian, Yajun
Objective: To investigate the clinical characteristics of cardiac cephalalgia and determine whether there is a more suitable alternative criterion. Method: Patients with cardiac cephalalgia diagnosed and treated from May 2019 to April 2021 in the First Affiliated Hospital of Zhengzhou University (Zhengzhou, China) were prospectively and consecutively collected, their clinical manifestations were analyzed, and compared with the 2018 diagnostic criteria. Results: A total of 30 patients were collected, including 16 males and 14 females. The onset age ranged from 31 to 84 years old, with a mean of 64.6 ± 11.9 years. Headache was more common in unilateral or bilateral frontotemporal, and the nature of pain includes pulsating, dull, stuffy pain, throbbing and so on. 80.0% were moderate to severe, 70% lasted less than half an hour, 76.6% had chest pain, 70% had chest tightness, 63.3% had sweating, and 36.6% had nausea. After treatment with drugs or coronary angiogenesis, except for one death, headache was fully or partially relieved in 29 patients. Conclusion: Cardiac cephalalgia is generally located in frontotemporal region, of moderate or severe intensity, with a pulsating or throbbing sensation, abating within 30 minutes, and has a good prognosis. Accompanying chest pain, chest tightness, and sweating should be included in the diagnostic criteria.